Public Health Messaging for Wildfire Smoke: Cast a Wide Net - Shellington, Erin M.; Nguyen, Phuong D. M.; Rideout, Karen; Barn, Prabjit; Lewis, Anna; Baillie, Margaret; Lutz, Sue; Allen, Ryan W.; Yao, Jiayun; Carlsten, Christopher; Henderson, Sarah B. (Frontiers in Public Health, 2022)
Wildfire smoke events are increasing in British Columbia (BC), Canada and environmental and public health agencies are responsible for communicating the health-related risks and mitigation strategies. To evaluate and identify opportunities for improving public communications about wildfire smoke and associated health risks we collaborated with end-users and developed a 32-question online survey. The survey was deployed province-wide from 29 September to 31 December 2020 following a severe wildfire smoke episode, which impacted large parts of BC. Using a convenience sample, we disseminated the survey through email lists, radio advertisements, a provincial research platform, and snowball methods. There were 757 respondents, who were generally representative of provincial demographics. Respondents indicated that they receive wildfire smoke messages from diverse sources, including: websites, social media, radio, and television. Radio was identified as the most important source of information for populations that may have increased exposure or health risks, including Indigenous respondents and those working in the trades. Respondents with lower educational attainment expressed that messaging should be simplified. Environmental and public health agencies should continue to share wildfire smoke messages using diverse methods, ideally tailoring the messages and methods to specific populations at risk for exposure and health effects.